Instructional Design of Classroom Instructional Skills Based on the ADDIE Model - Chang, LiLi; Mohamad Jafre Bin Zainol Abidin, (Technium Social Sciences Journal, 2024)
Abstract: With the rapid societal changes, the diversity of educational design approaches has increased. Educational professionals are now confronted with new challenges in training pre-service music teachers. They are required not only to employ emerging technologies for knowledge transfer but also to focus on cultivating teaching abilities to better meet the demands of prospective employers. This study utilizes the five phases of the ADDIE model (Analysis、Design、Develop、Implement、Evaluate) to design and develop a classroom teaching skills module aimed at enhancing the teaching abilities of pre-service music teachers. The application of the ADDIE instructional model in designing and developing modules for teaching pre-service music teachers is explored. The research findings indicate that the classroom teaching skills module has significantly improved the teaching abilities of pre-service music teachers. This study aims to reveal pathways for instructional reform in pre-service music teacher education, aligning it more effectively with societal needs and expectations.